Handedness, bilateral, and interdigit strength asymmetries in male climbers - Hartley, C.; Taylor, N.; Chidley, J.; Baláš, J.; Giles, D. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To determine whether there are bilateral and interdigit differences in the maximal force production of experienced climbers and whether these differences are mediated by ability level or preferred style of climbing.